Termalização e correlações quânticas nos contextos de sistemas quânticos abertos e cadeias de spins - Oliveira, Thiago Werlang de (2013)
In this thesis, we study the behavior of Quantum Discord in the contexts of open quantum systems and spin chains. Furthermore, we investigate the thermalization process of a spin chain due to interaction with the environment. First, we present a review on the concept of quantum correlation, beginning with the first ideas on non-locality, and leading to the measure of quantum correlations called Quantum Discord. Afterwards, we study the dynamics of the quantum correlations between two non-interacting qubits coupled to Markovian and non- Markovian thermal reservoirs. In the context of spin chains, we investigate the behavior of quantum correlations at finite temperatures, starting with a system composed of two interacting spins, described by XYZ model, in order to generalize this study to the case of infinite unidimensional spin chains, described by XY and XXZ models. In this context, we investigate the relationship between quantum correlations and quantum phase transitions present in these two models. We conclude this thesis with a study of the thermalization process of two interacting spins weakly coupled to independent bosonic thermal reservoirs, or to a single collective reservoir, besides presenting some results for larger systems, composed of an arbitrary number of spins.